2010
DOI: 10.1111/j.1365-2648.2010.05495.x
|View full text |Cite
|
Sign up to set email alerts
|

Stress, coping and satisfaction in nursing students

Abstract: Aim. This article is a report of a study conducted to explore the relationship between sources of stress and psychological well-being and to consider how different sources of stress and coping resources might function as moderators and mediators on well-being. Background. In most research exploring sources of stress and coping in nursing students, stress has been construed as psychological distress. Sources of stress likely to enhance well-being and, by implication, learning have not been considered. Method. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
131
1
11

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(159 citation statements)
references
References 45 publications
7
131
1
11
Order By: Relevance
“…(2) One study pointed to this lack of effectiveness, finding that students who used escape-avoidance strategies to deal with stress presented the greatest mean values of stress in all domains. (12) This fact was confirmed by another study, which demonstrated an inversely proportional association between escape-avoidance strategies and stress management/ solution: the more students used escape-avoidance strategies, the higher their mean levels of stress. (13) When students perceive themselves as lacking in theoretical and practical knowledge throughout their undergraduate education, feelings of insecurity emerge about their future professional life.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…(2) One study pointed to this lack of effectiveness, finding that students who used escape-avoidance strategies to deal with stress presented the greatest mean values of stress in all domains. (12) This fact was confirmed by another study, which demonstrated an inversely proportional association between escape-avoidance strategies and stress management/ solution: the more students used escape-avoidance strategies, the higher their mean levels of stress. (13) When students perceive themselves as lacking in theoretical and practical knowledge throughout their undergraduate education, feelings of insecurity emerge about their future professional life.…”
Section: Discussionsupporting
confidence: 69%
“…(5) In this sense, escape-avoidance is not a very effective strategy for managing stressful events. (12) This factor was the most prevalent among our sample, demonstrating that students try to escape from their problems using a delusionary or imaginary strategy, using escapist fantasies to minimize the severity of the situation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[17] Two studies, one conducted in UK and the other in the US, found that social support was a beneficial factor in helping nursing students cope with stress. [18,19] Similarly, in Turkey, a recent study found that nursing students who were seeking social support coped better with stress. [20] Further, a study found that nursing students with high EI also reported a large social support network.…”
Section: Introductionmentioning
confidence: 99%
“…따라서 간호대 학생의 임상실습 스트레스와 우울을 감소시키는 것이 임상실 습을 경험하는 학생의 정신적 건강증진은 물론 임상실습 만족 도 (Konstantinos & Christina, 2008;Moreira & Furegato, 2013;Park, 2009) 및 전공에 대한 만족도 향상 (Gibbons, Dempster, & Moutray, 2011;Ji, 2013)을 통해 임상실습적 응 능력 증진에도 기여할 것으로 생각된다.…”
unclassified